Immobilization of Pseudomonas putida A (ATCC 12633) cells: A promising tool for effective degradation of quaternary ammonium compounds in industrial effluents - Bergero, Maria Fernanda (2015)
Pseudomonas putida A (ATCC 12633) were encapsulated in Ca-alginate and their ability to degrade the quaternary ammonium compounds (QACs) tetradecylbenzyldimethylammonium chloride (C14BDMA), hexadecylbenzyldimethylammonium chloride (C16BDMA) and benzalkonium chloride (BAC) (a mixture 1:1 of C14BDMA and C16BDMA), was tested and compared with the degradation of the same compounds by freely suspended cells. Degradation was carried out in pH 7.4 buffered medium, at 30 °C with agitation at 100 rpm. After 24 h of incubation immobilized cells degraded 90 % of 35 to 315 mg l-1 of C14BDMA, C16BDMA and BAC, whereas free cells were unable to degrade concentrations above 35 mg l-1. Immobilized cells of P. putida removed 80 % QACs of an industrial effluent in 48 h under both sterile and non-sterile conditions. Degradation of QACs carried out using the non-sterilized effluent showed that the beads could be reused up to four cycles without changing the degradation efficiency. The reduction in the QACs concentration after treatment with immobilized cells can be correlated with the reduction in the phytotoxicity to Lactuta sativa seed germination and root elongation. We conclude that immobilized QACs-degrading bacteria represent a promising tool for bioremediation of QACs in industrial wastewater systems.